Emerging role of multimodality treatment in gall bladder cancer: Outcomes following 510 consecutive resections in a tertiary referral center. Issue 3 (20th September 2017) - Patkar, Shraddha; Ostwal, Vikas; Ramaswamy, Anant; Engineer, Reena; Chopra, Supriya; Shetty, Nitin; Dusane, Rohit; Shrikhande, Shailesh V.; Goel, Mahesh
Abstract : Background and Objectives: Gall bladder cancer (GBC) is a disease with high incidence in India. We analyzed the outcomes of patients with suspected GBC who underwent surgical exploration. Methods: Analysis of a prospectively maintained database of patients undergoing surgical exploration for clinic‐radiologically suspected GBC from January 2010 to August 2015. Outcomes as well as factors influencing survival were analyzed. Results: Five hundred and ten patients underwent surgery for suspected GBC. Of these 400 had histologically proven malignancy. Eighty patients were deemed inoperable. Radical cholecystectomy was performed in 153 patients, revision surgery for incidental GBC in 160 and port site excision in seven patients. A total of 112 received peri‐operative chemotherapy or chemoradiation. Majority were stage III (36%, n  = 144) and stage II (31.8% n  = 127). At a median follow up of 28.4 months, the median overall survival (OS) was not yet reached. Median disease free survival (DFS) was 33.4 months. Lymph node involvement, stage of the disease and resection status were the main factors influencing outcomes ( P  = 0.0001). Conclusion: Surgery alone is curative only for early GBC (Stage I). Combination of surgery and peri‐operative systemic therapy results in favorable outcomes even in stage II/III disease. Potentially, multimodality treatment may add meaningful survival for this disease with inherently aggressive tumor biology.